Kid presidents : true tales of childhood from America's presidents - Stabler, David; Horner, Doogie (Philadelphia, PA : Quirk Books, 2014)
A collection of anecdotes from the childhoods of United States presidents.
Includes bibliographical references (p. 208-211) and index.
Booklist
Publishers Weekly
School Library Journal
Booklist, September 2014
Horn Book, April 2015
Keywords: Presidents -- United States -- Juvenile literature; Presidents; Presidents -- United States